Sinapic Acid Attenuated Cardiac Remodeling After Myocardial Infarction by Promoting Macrophage M2 Polarization Through the PPARγ Pathway - Yang, Mei; Xiong, Jun; Zou, Qiang; Wang, Xi; Hu, Ke; Zhao, Qingyan (Frontiers in Cardiovascular Medicine, 2022)
Background Macrophage polarization is an important regulatory mechanism of ventricular remodeling. Studies have shown that sinapic acid (SA) exerts an anti-inflammatory effect. However, the effect of SA on macrophages is still unclear. Objectives The purpose of the study was to investigate the role of SA in macrophage polarization and ventricular remodeling after myocardial infarction (MI). Methods An MI model was established by ligating the left coronary artery. The rats with MI were treated with SA for 1 week or 4 weeks after MI. The effect of SA on bone marrow-derived macrophages (BMDMs) was also observed in vitro. Results Cardiac systolic dysfunction was significantly improved after SA treatment. SA reduced MCP-1 and CCR2 expression and macrophage infiltration. SA decreased the levels of the inflammatory factors TNF-α, IL-1α, IL-1β and iNOS and increased the levels of the M2 macrophage markers CD206, Arg-1, IL-10, Ym-1, Fizz-1 and TGF-β at 1 week after MI. SA significantly increased CD68+/CD206+ macrophage infiltration. Myocardial interstitial fibrosis and MMP-2 and MMP-9 levels were decreased, and the sympathetic nerve marker TH and nerve sprouting marker GAP43 were suppressed after SA treatment at 4 weeks after MI. The PPARγ level was notably upregulated after SA treatment. In vitro, SA also increased the expression of PPARγ mRNA in BMDMs and IL-4-treated BMDMs in a concentration-dependent manner. SA enhanced Arg1 and IL-10 expression in BMDMs, and the PPARγ antagonist GW9662 attenuated M2 macrophage marker expression. Conclusions Our results demonstrated that SA attenuated structural and neural remodeling by promoting macrophage M2 polarization via PPARγ activation after MI.